Implementing Sustainable Land Use Practices to Combat Desertification: A Comprehensive Analysis (Eurasian Research Bulletin, 2023)
Desertification, the degradation of land in arid, semi-arid, and dry sub-humid regions, poses significant challenges to global sustainability. This scientific article presents a comprehensive analysis of sustainable land use practices aimed at combating desertification. The paper begins with an explanation of desertification and its key concepts, followed by an introduction providing context and significance of the study. A literature review and methodology section elucidate current research and approaches to combat desertification. Results and discussion highlight the effectiveness of various sustainable land use practices, and a conclusion summarizes key findings. This article syerves as a valuable resource for policymakers, researchers, and land managers seeking to address desertification and promote sustainable land management.